2014
DOI: 10.1111/apt.13036
|View full text |Cite
|
Sign up to set email alerts
|

Differences in nephrotoxicity risk and renal effects among anti‐viral therapies against hepatitis B

Abstract: Summary Background Results are conflicting with respect to the renal effects of anti‐viral agents used for hepatitis B virus infection. Aim To compare short and long‐term renal effects in real‐life settings and to determine risk factors for renal impairment during treatment. Methods 2221 treatment‐naïve patients were enrolled. Among these, 895 (302 lamivudine, 27 telbivudine, 282 entecavir, 273 tenofovir and 11 adefovir initiated patients) had ‘repeated measures’ of creatinine (baseline, 1st, 6th, 12th and 24t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
4
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 24 publications
2
49
4
6
Order By: Relevance
“…The prevalence of nucleotide analogue-related proximal RTD in our study was higher than a previous report (15%), which may be due to the different criteria of proximal RTD in our study [17, 23, 24] and the other report [19]. On contrary, previous studies did not report significant reduction in renal function after long-term nucleotide analogue treatment in CHB [1315, 26]. However, comprehensive laboratory testing for proximal renal tubular function was not performed in these reports.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The prevalence of nucleotide analogue-related proximal RTD in our study was higher than a previous report (15%), which may be due to the different criteria of proximal RTD in our study [17, 23, 24] and the other report [19]. On contrary, previous studies did not report significant reduction in renal function after long-term nucleotide analogue treatment in CHB [1315, 26]. However, comprehensive laboratory testing for proximal renal tubular function was not performed in these reports.…”
Section: Discussioncontrasting
confidence: 97%
“…In clinical practice, TDF has been believed to be safer in terms of nephrotoxicity than ADV [12], and this has been supported by previous studies which showed that TDF was associated with a low incidence of renal dysfunction [1315]. On the other hand, subsequent small studies on the safety of ADV and TDF have shown that long-term treatment with ADV or TDF could potentially cause renal dysfunction, hypophosphatemia, and impaired renal tubular phosphate reabsorption [1619].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sebbene negli studi clinici randomizzati, controllati, in pazienti selezionati con epatite cronica B, il trattamento con TDF si sia dimostrato ben tollerato e senza segnalazioni di tossicità renale clinicamente significativa, l'esperienza clinica real life ha riportato casi di compromissione della funzione renale fino all'insufficienza renale e alla sindrome di Fanconi [6,7,[10][11][12][13][14][15][16][17][18][19][32][33][34][35][36][37][38][39]. Spesso i fattori di rischio per un peggioramento della funzione renale sono l'età avanzata, l'ipertensione arteriosa e una preesistente riduzione del filtrato glomerulare.…”
Section: Discussioneunclassified
“…Tra i NUC approvati, entecavir (ETV) e tenofovir disoproxil fumarato (TDF) sono raccomandati in prima linea nel trattamento dell'epatite cronica B, poiché entrambi sono antivirali potenti e con elevata barriera alla resistenza [1][2][3]. Negli studi registrativi e negli studi clinici a lungo termine, sia ETV che TDF hanno mostrato un profilo di sicurezza favorevole [4][5][6][7][8][9][10][11], anche se recentemente sono stati segnalati nella pratica clinica eventi avversi a livello Efficacia e sicurezza di entecavir dopo switch da tenofovir per comparsa di effetti collaterali renali M. Viganò renale e osseo nei pazienti trattati per lungo tempo con TDF [6,7,[10][11][12][13][14][15][16][17][18][19]. I meccanismi alla base della potenziale tossicità dei NUC sono legati alla loro capacità di inibire la DNA polimerasi ϒ mitocondriale umana quando le concentrazioni intracellulari dei NUC superano una soglia critica [12].…”
Section: Introduzioneunclassified